5-Methylcoumarin-4β-glucoside mitigated colon tumor progression in mice with AOM/DSS-induced colon carcinogenesis - Malami, Ibrahim; Alhassan, Alhassan Muhammad; Ahmed, Qamar Uddin; Shah, Syed Adnan Ali; Umar, Mohammed; Abubakar, Muhammad Salisu; Imam, Mustapha Umar; Abubakar, Bilyaminu (Elsevier, 2024)
Context The in vitro cytotoxicity profile of 5-Methylcoumarin-4β-glucoside (5-MC4βG) has been demonstrated to inhibit the proliferation of HT-29 adenocarcinoma cells. Aim: The need for newer and affordable chemotherapeutic agents is critical.